Active ex situ protection and reestablishment of Dianthus gratianopolitanus Vill. in the “Goździk siny w Grzybnie” reserve (Wielkopolska Province) - Jańczyk-Węglarska, Jolanta; Węglarski, Karol; Wiland-Szymańska, Justyna (Biodiversity: Research and Conservation, 2015)
The following paper presents the results of observations of the size and condition of cheddar pink (Dianthus gratianopolitanus Vill.) population in the “Goździk siny w Grzybnie” reserve (Wielkopolska Province), as well as active cultivation of the species in ex situ controlled conditions and its reestablishment supporting the natural, endangered population in the reserve